2020
DOI: 10.1007/s10100-020-00700-x
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: The concept of the qualitology and grey system theory application in marketing information quality cognition and assessment

Abstract: Unfortunately, the first name and family name of the author group have been incorrectly placed in the original publication. The complete correct names of author group should read as follows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…After years of development, the human resource service industry has become a supporting industry in the service industry, and its development scale is large; Majchrzak et al concluded from statistics that in the United States, outsourcing services account for more than one-half of the service industry; in addition, personnel outsourcing services account for the largest proportion of outsourcing services; and according to statistics, personnel services account for 10% of outsourcing services [7]. According to Mathematics -Grey System eory, the growth trend of HR service outsourcing in the U.S. is obvious in recent years, with an average annual growth rate of about 9%, and through the analysis of the growth trend in recent years, they predict that the future demand for HR services is still on the rise [8].…”
Section: State Of the Artmentioning
confidence: 99%
“…After years of development, the human resource service industry has become a supporting industry in the service industry, and its development scale is large; Majchrzak et al concluded from statistics that in the United States, outsourcing services account for more than one-half of the service industry; in addition, personnel outsourcing services account for the largest proportion of outsourcing services; and according to statistics, personnel services account for 10% of outsourcing services [7]. According to Mathematics -Grey System eory, the growth trend of HR service outsourcing in the U.S. is obvious in recent years, with an average annual growth rate of about 9%, and through the analysis of the growth trend in recent years, they predict that the future demand for HR services is still on the rise [8].…”
Section: State Of the Artmentioning
confidence: 99%
“…For example, some scholars believe that local governments should be the first to achieve the transfer and coordination of monitoring information among relevant departments in the prevention and control of WP, especially in the prevention and control of WP in river basins, and that the unification of WP monitoring information among various departments determines the merits of pollution control programmes. Government departments should hold regular joint meetings to exchange regulatory information, strengthen the comprehensive research and analysis of all regulatory information, and improve the level of global and local relations, especially in the allocation of regional resources, all of which are fundamental to decision-making for WP prevention and control [3][4]. Through research and empirical analysis of WP risk management theory, some scholars have concluded that WP risk management should be predicted before a pollution event occurs, so that a potentially large crisis incident can be transformed into a low-risk incident and long-term management of WP can be achieved, thus defusing the WP crisis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Квалітологія -наука про якість, заснована на системі взаємопов'язаних наукових принципів теорії управління якістю, кваліметрії і метрології (Зубрецкая, 2015). Її витоки можна знайти у філософських ученнях: онтології, що описує спосіб існування і структуру реальності; епістемології, що стосується змісту, меж, методів та об'єктів людського пізнання; аксіології -ученні про цінність (Majchrzak et al, 2020). Оцінювання якості нині розуміється і здійснюється щодо товарів, послуг, даних, виробничих процесів і виробництва загалом (Juran, 1998).…”
unclassified